PENERAPAN METODE ROLE PLAYING PADA MATA PELAJARAN MENGOPERASIKAN PERALATAN TRANSAKSI DI LOKASI PENJUALAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI PEMASARAN 3 SMK NEGERI 1 SUKOHARJO TAHUN AJARAN 2015/2016 - Muhammad Faqih Fida Ul Haq; Soetarno Joyoatmojo; Sri Wahyuni (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aims of this research is to increase the learning outcomes of transaction operating tools lesson on sale location of XI Marketing-3 Grade SMKN 1 Sukoharjo through the applying of the Role Playing method.This research was Classroom Action Research (CAR). This research was conducted in two cycles, wich consist planning, action, observation and reflection. The subjects of this research was XI Marketing-3 Grade of SMKN 1 Sukoharjo which consists 36 students. The source of data was from the students, the teachers, and the documents. Technique of collecting data was observation, test, documentation and interviews. Techniques for the validity of the data using triangulation of data sources. The data analysis used descriptive analysis techniques, qualitative analysis techniques and comparative description.The results of the research showed that applying the method of Role Playing can increase the learning outcomes of transaction operating tools on sale location of XI Marketing-3 Grade of SMKN 1 Sukoharjo in Academic Year 2015/2016. It was proved there is increasing in cycle I and cycle II. Before applying the method of Role Playing the average score of the classroom was 70 with precentage of success 36.11%. In the cycle I the average score increased to 80.75 with precentage of success 77.78% and in the cycle II the average score of the classroom increased to 87.25 with precentage of success 88.89%. The conclusion of this research was applying the method of Role Playing can increase the student's learning outcomes of transaction operating tools on sale location of XI Marketing-3 Grade SMKN 1 Sukoharjo.